TINJAUAN PERSEPSI ORANG TUA TERHADAP PENDIDIKAN ANAK USIA DINI DI DESA CIANAGA KECAMATAN KABANDUNGAN - Rahmi Kemala Handayani; Elan Elan; Sima Mulyadi (Universitas Pendidikan Indonesia (UPI), 2022)
Cianaga Village is one of the villages in the Kabandungan sub-district, Sukabumi Regency. Its location which is still rural, the educational background of the parents is still low, and the unavailability of a formal PAUD institution is an interesting phenomenon to study. The general purpose of this research is to describe the perception of parents in Cianaga Village on Early Childhood Education from the results of the questionnaire measurements distributed. This research was conducted using a quantitative approach to the survey method. The study was conducted by distributing questionnaires to parents as research samples. Aspects that are used as a measure are the nature, objectives and functions, as well as the path for the implementation of Early Childhood Education. Based on the results of data analysis, the perception category of parents in Cianaga Village towards Early Childhood Education is